Peatland forest monitoring and management solution in Peninsular Malaysia: optimal parameters for LoRa data - Saleh, Nur Luqman; Sali, Aduwati; Jiun Terng, Liew; Syed Ahmad Abdul Rahman, Sharifah Mumtazah; Mohd Ali, Azizi; Mohd Ali, Borhanuddin; Mohd Razali, Sheriza; Nuruddin, Ahmad Ainuddin; Ramli, Nordin (Ain Shams University, 2025)
Peatland forest fires threaten biodiversity, ecosystems, and human health in Southeast Asia, especially during the dry season. Limited in-situ data collection necessitates Long Range (LoRa) sensor-based remote monitoring for its long-range communication, low power consumption, and cost-effectiveness. However, dense vegetation affects Low-Power Wide Area Network (LPWAN) signal propagation through scattering, reflection, and diffraction, impacting data transmission. This study investigates LoRa RF propagation in peatland environments through a measurement campaign at Raja Musa Forest Reserve (RMFR), Selangor. File transfer success rate (FT%) across various land-cover types was analyzed using six Data Rate (DR) and Spreading Factor (SF) configurations. Results show that DR5/SF7 and DR0/SF12 achieve over 80% FT% in moderate and dense vegetation, respectively. The findings enhance LoRa RF planning in challenging ecosystems, offering practical guidelines to improve data transmission reliability in RMFR and other peatlands.